The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1128/spectrum.01854-22
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of New β-Lactam–β-Lactamase Inhibitor Combinations and Comparators against Clinical Isolates of Gram-Negative Bacilli: Results from the China Antimicrobial Surveillance Network (CHINET) in 2019

Abstract: Enterobacterales , Pseudomonas aeruginosa , and Acinetobacter baumannii are the most common Gram-negative bacilli to cause nosocomial infections throughout the world. Due to their large public health and societal implications, carbapenem-resistant A. baumannii (CRAB), carbapenem-resistant P. aeruginosa (CRPA), and carbapenem-resistant and third-generation-cephalosporin-resistant Enterobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Some studies have shown similar activity of CAZ/AVI and PB against CR-GNB (in CRE: 97.5% and 90.5% respectively; in CRPA98.2% and 96.9% respectively and in CRAB 96.6% and 96.6% respectively. 43 On the other hand, a recent meta-analysis suggests that CAZ-AVI treatment the treatment was more efficient thanpolymyxins in CRE. However, in this meta-analysis were included only observational studies with small series of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown similar activity of CAZ/AVI and PB against CR-GNB (in CRE: 97.5% and 90.5% respectively; in CRPA98.2% and 96.9% respectively and in CRAB 96.6% and 96.6% respectively. 43 On the other hand, a recent meta-analysis suggests that CAZ-AVI treatment the treatment was more efficient thanpolymyxins in CRE. However, in this meta-analysis were included only observational studies with small series of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The combination was effective against isolates of E. coli, K. pneumoniae , K. oxytoca , and Proteus mirabilis that produced ESBL, AmpC, and CMY-like cephalosporinases. Additionally, the combination has demonstrated efficacy against bacteria containing the genes bla KPC-2 , bla KPC-3 , or bla OXA-48 ( Yahav et al., 2020 ; Guo et al., 2022 ).…”
Section: Broad-spectrum β -Lactam- β ...mentioning
confidence: 99%
“…Numerous studies have noted the emergence of CAZ-AVI resistance following exposure, i.e., as a result of increased ceftazidime hydrolysis caused by mutations in the β -loop of K. pneumoniae carbapenemase (KPC) enzymes that are only partially inhibited by avibactam ( Zhanel et al., 2018 ; Guo et al., 2022 ; Hernández-García et al., 2022 ).…”
Section: Broad-spectrum β -Lactam- β ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 86.1% of the CRE strains and 89.8% of CR- K. pneumoniae isolates were inhibited by CEFI/ZIDE at 2 mg/L [ 128 ]. In contrast, most CRE and CR- P. aeruginosa isolates were susceptible to CEFI/ZIDE [ 129 ]. At MICs ≤ 8 mg/L, only 34% of CR- A. baumanii isolates were sensitive to CEFI/ZIDE [ 130 ].…”
Section: Antimicrobials In Phase 3 Clinical Trialsmentioning
confidence: 99%